006 Coronary heart disease mortality in The Netherlands from 1972 to 2007. (16th November 2010) - Vaartjes, I; O'Flaherty, M; Bots, M; Capewell, S
Abstract : Background: Coronary heart disease (CHD) mortality has steadily declined since the early 1970s in The Netherlands. Recent work suggests that in some Western countries the rate of decline in some groups has begun to decrease and may be starting to plateau or even reverse. These changes may be a result of changes in the pattern for major cardiovascular risk factor trends. Methods: Data for all deaths between 1972 and 2007 in The Netherlands were grouped by year, sex, age at death and contemporaneous ICD code for CHD as cause of death. Per age-sex-group a joinpoint regression was fitted to detect points in time at which significant changes in the trends occur. For every period the linear slope of the trend, p-value, observed number of deaths (min-max) and observed CHD mortality rates (min-max) were tabulated. Furthermore we calculated the change in observed CHD mortality rate per period. Results: Between 1972 and 2007, the age-adjusted CHD mortality rates decreased overall by 75.6% in men and by 75.7% in women. In men aged 35–54 the decline in CHD mortality rate attenuated in the period 1993–1999 (change in CHD mortality rate in period 1980–1993: −0.53 and in period 1993–1999: −0.16). In women aged 35 to 54 the decline in CHD mortality rate attenuated in the period 1989–2000 (change in CHD mortality rate in period 1979–1989: −0.58 and in period 1989–2000: −0.02). After 1999–2000 CHD mortality rate further declined in both gender (in men change in CHD mortality rate in period 1999–2007 was −0.46, in women change in CHD mortality rate in period 2000–2007 was −0.38). Conclusions: Evidence from several Western countries suggests some levelling out of CHD mortality rates among younger men and women and warn that CHD mortality rates in these groups may be starting to increase. In the present study attenuation of the decline in CHD mortality among men and women aged 35–54 years has been observed starting in the mid 90s. Furthermore, we observed that after a period where the decline in CHD mortality was attenuated, an increase in the pace of decline was observed. In order to explain these recent changes in CHD mortality rates, a detailed analysis of recent changes in cardiovascular risk factors is urgently required.